The school evaluation in Galicia: specific actions of the educational inspectorate - Fernández Álvarez, Marcos Antonio; Veloso Carnero, Rubén (Avances en Supervisión Educativa, 2023)
The basic characteristics of the educational evaluation model in Galicia are indicated, through a general analysis and the presentation of specific evaluation actions. An internal and external evaluation plan is presented, based on a standardised quality model through the ISO standard, for Integrated Vocational Training and Special Education Centres (Music Conservatories and Art Schools), and two specific evaluation actions: the external evaluation of the teaching departments of the educational centres, and the evaluation of the PROA+ Programme. The planning, procedures and strategies of the evaluation actions are shown, as well as the instruments and models used. The participation of education inspectors in this evaluation process in Galicia is specified, highlighting the help they contribute to the improvement of educational centres and the plans, programmes and projects that are developed.
Keywords: school evaluation; evaluation reports; self-evaluation; internal evaluation; external evaluation; school autonomy; evaluation model